Fodor's Prague 2023 - Johnston, Raymond (Travel writer); Reaney, Joseph; Rigby, Jennifer (Fodor's travel., 2023)
Whether you want to visit Prague Castle, walk across the famed Charles Bridge, or enjoy Czech beer in the beer capital of the world, the local Fodor's travel experts in Prague and across the Czech Republic are here to help! Fodor's Prague: with The Best of the Czech Republic guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time. This new edition has been fully-redesigned with an easy-to-read layout, fresh information, and beautiful color photos.